THE EFFECT OF USING SENSORY IMAGES AND QUESTIONING STRATEGIES ON THE STUDENTS’ ABILITY IN READING COMPREHENSION - Lubis, Yani (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2019)
Abstract Sensory images strategy talks about experience, experience is significant aspect for background knowledge. So, sensory images strategy guides the students to represent of their experience in their memories. The Questioning Strategy is a way of forming questions as you read in order to deepen understanding and enjoyment of the text. The Questions have many deals with clarifying the meaning or a phrase or passage, exploring important themes, considering the author’s technique, or learning more about something you find that interesting. The second part of the Questioning Strategy is finding an answer, either on your own or with the help of a teacher or friend. The Aims of Study were to know Students’ Understanding to the text when taught with Sensory Images strategy and Students’ Understanding to the text when taught with Questioning strategy. To know differences the students’ ability in reading comprehension when taught with Sensory Images and Questioning strategies.